The Impact of Rainfall Fluctuations on the Trophic of Maninjau Lake Based on the Carlson Index and The Comprehensive Index (CTSI) - Arlina, Lia; Komala, Puti Sri; Silvia, Shinta (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Maninjau Lake is experiencing increased eutrophication levels, negatively impacting water quality and the balance of its aquatic ecosystems. One of the factors that is thought to play a role in accelerating the process is rainfall fluctuation, which affects nutrient input from the water catchment area. This study aims to analyze the effect of rainfall fluctuation on the trophic status of Maninjau Lake using the Carlson Trophic State Index (TSI) and Comprehensive Trophic State Index (CTSI) methods. Water sampling was conducted at 10 stations over three periods: September 2022, January 2023, and March 2023, which represented seasonal variations. The parameters measured included chlorophyll-a, total phosphorus (TP), total nitrogen (TN), chemical oxygen demand (COD), and Secchi depth according to national standards. Rainfall data were obtained from BMKG stations and correlated with trophic index values. Results showed TSI values ranged from 55–72 and CTSI between 60–75, indicating eutrophic to hypereutrophic conditions. The highest trophic status occurred in periods of high rainfall, with a strong positive correlation between rainfall intensity and nutrient increase (r = 0.999 for TSI; r = 0.989 for CTSI). Rainfall plays a role as the main hydrometeorological driver of trophic dynamics, so adaptive management is needed to mitigate the impact of eutrophication under climate variability.